Prevalence of Chlamydia trachomatis infection among women in a Middle Eastern community - Ghazal-Aswad Saad; Badrinath Padmanabhan; Osman Nawal; Abdul-Khaliq Samar; Mc Ilvenny Shirley; Sidky Islam (BMC, 2004)
Abstract Background Common vaginal infections that manifest in women are usually easily diagnosed. However, Chlamydia infection is often asymptomatic, leading to infertility before it is detected. If it occurs in pregnancy, it could lead to significant neonatal morbidity. It may also play a role with other viral infections for e.g. Human Papilloma Virus in the development of cervical cancer. The objective of this study was to determine the prevalence of Chlamydia infection in women undergoing screening for cervical abnormalities as a part of a research project in primary and secondary care institutions in the United Arab Emirates. Methods In this cross sectional study married women attending primary and secondary care participating in a large nationwide cervical abnormalities screening survey were offered Chlamydia testing using a commercially available test kit. This kit uses a rapid immunoassay for the direct detection of Chlamydia trachomatis antigen in endocervical swab specimens. As this study was performed in a traditional Islamic country, unmarried women were excluded from testing, as the management of any positive cases would create legal and social problems. All married women consenting to take part in the study were included irrespective of age. Results Of 1039 women approached over a period of eight months 919 (88.5%) agreed to participate. The number of women in the 16 to 19 years was small (0.01%) and 30% were aged over 40 years. The prevalence of Chlamydia infection in this study was 2.6% (95% confidence interval 1.2-3.3%), which was marginally higher in women screened in secondary care (p = 0.05). Conclusion This is one of the few reports on the prevalence of Chlamydia infection in women from the Middle East. Due to cultural and social constraints this study excluded a large proportion of women aged less than 19 years of age. Hence no direct comparisons on prevalence could be made with studies from the West, which all included younger women at high risk of Chlamydia. However this study emphasizes the importance of cultural factors while interpreting results of studies from different cultures and communities.